Social exclusion and care for the elderly: Theoretical concepts and changing realities in European welfare states - Hildegard Theobald (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
How approaches in elderly care should be structured to counteract processes of social marginalisation in old age is in the focus of this discussion paper. On a theoretical basis the paper draws on concepts of social exclusion developed in international comparative welfare state research. For the analysis of processes of social exclusion in old age, the ageing process is defined on a wide basis ranging from genetic, social, cultural to environmental components. The term inclusive care describes characteristics of approaches in elderly care, which enable processes of social exclusion to be counteracted. Approaches in elderly care have been re-structured in most member countries of the European Union since the beginning of the 1990s. With the background of the defined characteristics of inclusive care modes of financing, access criteria and procedures, diversification and integration of service facilities and offers as well as the combination with informal care are investigated. The characteristics decisive for inclusive care are defined such as universal accessibility related to social rights, a diversified and integrated care system, a social model of care delivery and the acknowledgement, support and cooperation with informal carers. The findings prove the difficulties and obstacles encountered by certain EU-member countries to fulfil the criteria. Furthermore, according to their risk of experiencing processes of social exclusion, inequalities among different groups of elderly people have become apparent. – – Im Zentrum des Discussion Papers steht die Frage nach adäquaten Ansätzen in der Alten-betreuung zur Verhinderung von sozialer Marginalisierung älterer Menschen. Konzeptionell wird auf Ansätze der international vergleichenden Wohlfahrtsstaatsforschung zur Debatte um soziale Ausgrenzung (social exclusion) zurückgegriffen, die auf die beiden Bereiche Altern und Betreuung älterer Menschen zugespitzt werden. Die Analyse sozialer Aus-grenzung erfordert eine Definition des Alterns-Prozesses, der neben genetischen insbesondere soziale, kulturelle und umweltbezogene Komponenten einschließt. Der Begriff Inclusive Care benennt Charakteristika der Altenbetreuung, die es ermöglichen, Prozessen sozialer Ausgrenzung im Alter entgegenzuwirken. Seit den 1990er Jahren wurden in den meisten Mitgliedsländern der Europäischen Union die Ansätze in der Altenbetreuung restrukturiert. Vor dem Hintergrund der Definition der Charakteristika von Inclusive Care werden Finanzierung, Zugangskriterien, Diversifikation und Integration von Dienstleistungen sowie die Verbindung zur informellen Pflege untersucht. Dabei erweisen sich ein universeller Zugang zu Dienstleistungen verbunden mit sozialen Rechten, ein ausdifferenziertes aber integriertes Versorgungssystem, ein soziales Modell der Versorgung und die Anerkennung, Unterstützung sowie die Kooperation mit informell Pflegenden als entscheidend. Die Ergebnisse zeigen aber auch die Schwierigkeiten in unterschiedlichen europäischen Ländern auf, die Anforderungen zu erfüllen. Deutlich werden zudem Ungleichheiten zwischen verschiedenen Gruppen älterer Menschen, die in unterschiedlicher Art und Weise und Ausmaß von dem Risiko sozialer Ausgrenzung bedroht sind.
Keywords: 300; Alte Menschen; Altenhilfe; Soziale Isolation; Europa